The impact of national comprehensive medical reform on residents' medical expenses: Evidence from China - Nie, Changfei; Feng, Yuan (Frontiers in Public Health, 2023)
Residents' high medical expenses is the core challenge that needs to be solved urgently in China's medical reform for a long time. Based on the panel data of 30 provinces in Chinese Mainland during 2011-2019, we evaluate the impact of China's national comprehensive medical reform pilot policy on residents' medical expenses by using the difference-in-differences model. The results show that the pilot policy was generally conducive to reducing residents' medical expenses, resulting in a reduction of 2.13% in per capita medical expenses for inpatients, but the effect on per capita medical expenses for outpatients was insignificant. Mechanism analysis shows that hospital competition and institutional environment played a moderating role in the effect of the pilot policy on residents' medical expenses reduction. The more intense the hospital competition and the better the institutional environment, the more significant of the reduction effect. In addition, the reduction effect of the pilot policy was greater in the central provinces, the provinces with poor medical infrastructure, and the provinces with strong financial strength. This study provides useful policy insights for deepening medical reform and reducing residents' medical expenses.